2007
DOI: 10.1002/ijc.22293
|View full text |Cite
|
Sign up to set email alerts
|

Phosphocholine as a biomarker of breast cancer: Molecular and biochemical studies

Abstract: The discovery of metabolic and molecular markers that help improving the detection and diagnosis of breast cancer is an important goal to be achieved. A high composite-choline signal in magnetic resonance spectra of breast lesions has been demonstrated to improve the accuracy of breast cancer diagnosis. In the present study we revealed the principal molecular and biochemical steps associated with the induction of choline metabolism and phosphocholine accumulation in human breast cancer cell-lines in comparison… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

20
223
4
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(251 citation statements)
references
References 65 publications
20
223
4
4
Order By: Relevance
“…3C), suggesting disruptions to metabolic pathways downstream of EDI3. Previous studies have shown that the activity of CK, which generates PC from choline, is increased in cancer cells (4,7,(10)(11)(12). EDI3 acts upstream of CK, adding further evidence that disruption of this metabolic pathway can play a significant role in tumor progression.…”
Section: Edi3 Predicts Metastasis In Endometrial and Ovarian Cancermentioning
confidence: 84%
See 2 more Smart Citations
“…3C), suggesting disruptions to metabolic pathways downstream of EDI3. Previous studies have shown that the activity of CK, which generates PC from choline, is increased in cancer cells (4,7,(10)(11)(12). EDI3 acts upstream of CK, adding further evidence that disruption of this metabolic pathway can play a significant role in tumor progression.…”
Section: Edi3 Predicts Metastasis In Endometrial and Ovarian Cancermentioning
confidence: 84%
“…Targeting CK with inhibitors resulted in antimitogenic and antiproliferative effects (13). It has also been reported that an increased rate of choline transport may be responsible for the increased PC levels (10,14,15). However, gene-expression analysis of members of the three choline transporter families in ovarian cancer cells showed no differential levels for the high-affinity transporter families compared with normal cells (7).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…[6][7][8][9][10] With respect to the latter, recent studies have suggested that elevated choline metabolism, including increased phosphocholine (PC) levels, is associated with worse prognosis. 9,[11][12][13] However, the mechanism of how higher PC levels contribute to cancer progression is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…3 An amount of different phospholipids has been studied as biomarkers for ovarian 4 and breast cancers. 5 The role of metabolites and lipids such as Phosphatidylcholines (PCs) and Phosphoethanolamines (PEs) as breast cancer biomarkers has been investigated by Eliyahu et al, 6 Hilvo et al, 7 and Butczies et al 8 Separation of breast cancer tissues from normal breast tissues was demonstrated to be feasible with high sensitivity and specificity. The same PC and PE biomarkers were also detected from urine samples by Kim et al 9 They succeeded to measure PC and PE lipids with nanoflow liquid chromatography tandem mass spectrometry.…”
mentioning
confidence: 99%